Does population agglomeration of urban clusters boost total factor productivity of enterprises? Evidence from listed companies in China - Weige Xiao; Chunli Ji; Qing Shao; Songlin Zhang (PLoS ONE, 2025)
Introduction The role of agglomeration economics in enhancing productivity is well-recognized, yet the influence of population agglomeration of urban clusters on Total Factor Productivity (TFP) within the enterprises of the agglomerates remains a relatively uncharted area. This study aims to investigate the impact of population agglomeration of urban clusters on the TFP of enterprises and its underlying mechanisms. Data sources The data for firm-levelwere sourced from the CSMAR and Wind databases. City-level data were obtained from the China City Statistical Yearbook and the China Urban Construction Statistical Yearbook. Research method A fixed-effects model was employed. Key findings ① The baseline regression shows that population agglomeration of urban clusters significantly bolsters the TFP of enterprises. ② Heterogeneity tests further reveal that this simulative effect is more pronounced in the eastern region, inter-provincial city clusters, and large cities.. ③ The underlying mechanisms indicate that population agglomeration of urban clusters, through its market effects and scale economic effects effectively reduce production costs, thereby boosting overall production efficiency and promoting the elevation of TFP in enterprises. Policy implications To scientifically guide the orderly population agglomeration of urban clusters, it is essential to fully leverage the marketization effects of population agglomeration of urban clusters and deepen the specialization and division of labor within these clusters. This study provides empirical evidence and important references for policymakers to effectively leverage the marketization and specialization effects of urban cluster population agglomeration, thereby promoting new urbanization and achieving high-quality development.